Makna Tanah Menurut Suku Dayak Bahau Busaang dan Teologi Lingkungan - Vinsensius Huvang; G. Simon Devung; Silpanus (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2020)
The purpose of the study is: Finding the meaning of land according to the Dayak Bahau Busaang and comparing it to the meaning of land according to the view of the Catholic Church in terms of Environmental Theology. Then making a reflective review of the meaning of land from the perspectives of the two entities as a rationale for environmental catechesis related to land, specifically on the environmental catechesis in the parish of Santa Maria Long Hubung.This research was conducted in the village of Long Hubung Ulu, Long Hubung District, Mahakam Ulu Regency using a descriptive qualitative approach. The data collection techniques used are in-depth interviews and secondary data collection and informants is this study were twelve informants. Based on the results of this study, it was concluded that the Dayak Bahau Busaang Long Hubung Ulu and the Catholic Church have similarities in interpreting land because they both contain physical, social and religious aspects in their perspectives that illustrate the relationship between all creatures and the Creator and a symbol of hereditary interaction with the environment.